Comparison of patient satisfaction rates for the malleable and two piece-inflatable penile prostheses - Kılıçarslan, Hakan (Turk J Urol, 2014)
OBJECTIVE: To compare patient/partner satisfaction with AMS 600–650 and AMS Ambicore penile implants (American Medical Systems, Minneapolis, USA) in patients with erectile dysfunction. MATERIAL AND METHODS: The modified Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) questionnaires at six months after implantation of 46 patients who underwent AMS 600–650 (n=23) or Ambicore placement (n=23) between 1/1/2008 and 1/1/2013 were analyzed. RESULTS: The percentages of patients with AMS 600–650 who reported to be satisfied, very satisfied and neither satisfied nor dissatisfied with their prostheses were 34.78% (n=8), 30.43% (n=7) and 34.78% (n=8), respectively. For patients with AMS Ambicore, these percentages were 73.91% (n=17), 13.04% (n=3) and 13.04% (n=3), respectively. These overall satisfaction rates were significantly different between patients with AMS 600–650 and Ambicore (p=0.013). For patients with AMS 600–650, the percentages of patients who reported to be very likely, neither likely nor unlikely, or very unlikely to continue using their prosthesis were 30.43% (n=7), 34.78% (n=8), and 34.78% (n=8) while for patients with AMS Ambicore, these percentages were 65.21%, 21.33%, and 13.04%, respectively. These percentages were different between patients with AMS 600–650 and Ambicore (p=0.018). CONCLUSION: The two-piece inflatable penile prosthesis was found to be more successful in overall satisfaction and more likely for continued use when compared to the malleable penile prosthesis.